2017
DOI: 10.1111/jfpp.13309
|View full text |Cite
|
Sign up to set email alerts
|

Tomato seed oil for edible use: Cold break, hot break, and harvest year effects

Abstract: In the tomato juice and sauce industries, tomatoes are submitted to a hot break or a cold break thermal treatment. Tomato seed is considered waste but could become an important source of edible oil. A 3‐year study was conducted. The studied properties were free acidity (max 1.26%), peroxide value (max 6.14 meq O2/kg oil), p‐anisidine value (0.40–13.45), Totox (3.85–24.68), saponification value (187.84–198.90), total phenols (212–532 mg/kg), and refractive index (1.4707–1.4723). DPPH· was always higher than 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
6
20
1
Order By: Relevance
“…The FFA value of the oil (0.46 oleic acid %) did not exceed the maximum limit of 4% (oleic acid) set by regulations [69]. Our finding partially agrees with the results of Giuffrè et al [67] (0.24-1.26%). The iodine number of cold-pressed tomato pomace oil was 109.02 g/100g.…”
Section: Physicochemical Properties Of Cold-pressed Tomato Pomace Oilsupporting
confidence: 92%
See 3 more Smart Citations
“…The FFA value of the oil (0.46 oleic acid %) did not exceed the maximum limit of 4% (oleic acid) set by regulations [69]. Our finding partially agrees with the results of Giuffrè et al [67] (0.24-1.26%). The iodine number of cold-pressed tomato pomace oil was 109.02 g/100g.…”
Section: Physicochemical Properties Of Cold-pressed Tomato Pomace Oilsupporting
confidence: 92%
“…The peroxide value (2.47 meq O 2 / kg) was lower than the allowed limit of 15 meq O 2 /kg defined in the regulation [69]. This value partially agrees with the findings of Giuffrè et al [67] who reported a wide range of peroxide values (0.97 meq O 2 /kg-6.14 meq O 2 /kg) for tomato seed oils obtained through hot and cold break processes. Compared to our finding, Shao et al [72] reported lower peroxide value (0.63 meq O 2 /kg) in hexane-extracted tomato seed oil, while Yilmaz et al [44] declared higher peroxide values (3.93-4.52 meq O 2 /kg) for cold-pressed tomato seed oils.…”
Section: Physicochemical Properties Of Cold-pressed Tomato Pomace Oilsupporting
confidence: 88%
See 2 more Smart Citations
“…For this reason many authors suggest applying more than one assay to evaluate antioxidant activity. In the present study we applied DPPH assay and FRAP assay which are two of the most common tests used on many matrices such as common orange [13] blood orange juice [10], edible vegetable oils and potential industrial vegetable oils [36][37][38], apples, bananas, strawberries, kiwifruit, cauliflower [39]. Vitamin C and flavonoids are the most important antioxidants in bergamot juice and show an inverse ratio during fruit ripening: the vitamin C showed a decreasing trend (Table 3) in opposition to total flavonoid content which increased with harvest date (Table 4).…”
Section: Dpph Assay and Frap Assaymentioning
confidence: 99%